Comparative Study on the Various Hydrolysis and Fermentation Methods of Chlorella vulgaris Biomass for the Production of Bioethanol - Megawati Megawati; Zuhriyan Ash Shiddieqy Bahlawan; Astrilia Damayanti; Radenrara Dewi Artanti Putri; Bayu Triwibowo; Haniif Prasetiawan (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
One of the microalgae that can be potentially used to produce bioethanol is Chlorella vulgaris, as it is rich in carbohydrates. However, the carbohydrates in C. vulgaris cannot be converted directly into ethanol. This study aimed to investigate the chemical and enzymatic hydrolysis of C. vulgaris, which is subsequently followed by fermentation. The catalysts used in the chemical hydrolysis were hydrochloric acid, sodium hydroxide, and potassium hydroxide, while the enzymes used were the mixture of alpha-amylase + glucoamylase, alpha-amylase + cellulase, and alpha-amylase + glucoamylase + cellulase. The hydrolysate obtained from chemical hydrolysis was fermented through Separate Hydrolysis Fermentation (SHF), while the one from enzymatic hydrolysis was fermented through Simultaneous Saccharification and Fermentation (SSF), in which both processes used S. cerevisiae. After undergoing five hours of enzymatic hydrolysis (using alpha-amylase + glucoamylase), the maximum glucose concentration obtained was 9.24 ± 0.240 g/L or yield of 81.39%. At the same time and conditions of the substrate on chemical hydrolysis, glucose concentration was obtained up to 9.23 + 0.218 g/L with a yield of 73.39% using 1 M hydrochloric acid. These results indicate that chemical hydrolysis is less effective compared to enzymatic hydrolysis. Furthermore, after 48 hours of fermentation, the ethanol produced from SHF and SSF fermentation methods were 4.42 and 4.67 g/L, respectively, implying that producing bioethanol using the SSF is more effective than the SHF method.